Focal therapy: definition and rationale. Issue 3 (25th May 2022) - Clark, Roderick; Klotz, Laurence
Abstract : Purpose of review: The role of focal therapy for the treatment of prostate cancer is expanding in clinical practice. The aim of this review is to introduce readers to controversies in the use of focal therapy and its rationale. Recent findings: There is a growing body of literature regarding the short-term and medium-term cancer control parameters and quality of life outcomes. These are mostly observational studies without a comparative arm. There is a need for high-quality randomize control trials comparing these treatments to definitive standard of care interventions (e.g. surgery or radiotherapy) in appropriate patient populations. Summary: Focal therapy for prostate cancer has become an established therapeutic strategy. Evidence continues to accrue regarding its effectiveness. It is a useful treatment option for the appropriately selected patient, with the appeal of improved quality of life compared with standard therapies.